Effects on primary stability of three different techniques for implant site preparation in synthetic bone models of different densities. Issue 9 (November 2016) - Möhlhenrich, S.C.; Kniha, K.; Heussen, N.; Hölzle, F.; Modabber, A.
Abstract: Preparation of implant sites affect the primary stability of implants that is necessary for osseointegration. We have investigated the effect on the primary stability of implants of three techniques used to prepare the site for implants in synthetic bone models of different densities. A total of 540 implants of varying diameters (3.3 (narrow), 4.1 (standard), and 4.8 (wide) mm) and lengths (8 or 12 mm) were inserted into three artificial bone blocks (the density of which decreased from D2, D3, to D4), and we compared conventional, fully-guided, and condensing preparation of the site. After insertion, primary stability was measured using resonance frequency analysis. There were significant differences between conventional and condensing procedures (p <0.0001 in all cases) and between fully-guided and condensing procedures (p < 0.01 in all cases), but there were no differences between fully-guided and conventional procedures when short implants were used, with a standard or wide diameter in low-density bone blocks (D3 and D4). In low-density bone blocks (D3 and D4) wide implants (4.8 mm) compared with narrow (3.3 mm) resulted in significantly better primary stability (p < 0.0001 in all cases). Fully-guided preparation of the implant site is associated with increased primary stability, but is not an alternative to bone condensing. Use of longer or wider implants can increase primary stability, but the effect is less pronounced after bone condensing.